Synthesis, Characterization and Study of Phenol Adsorption Over MnOx- CeO2 - D'Alessandro, Oriana (2014)
Five MnOx-CeO2 samples with a molar ratio Mn-Ce between 0 and 100% were obtained by coprecipitation. The samples, which were called 10/0, 7/3, 5/5, 3/7, 0/10, were characterized by XRD, FTIR, XPS, specific surface area and TPR. Phenol was selected as pollutant. The adsorption of phenol from aqueous solution on Mn-Ce samples was investigated in a batch reactor at 25 and 50° C. The adsorption isotherms were described by Langmuir and Freundlich isotherm models and both model fitted. The characterization results showed the formation of solid solution where Mn3+ replaces Ce4+. The most active solid was Mn-Ce 7/3. The results showed that the adsorption process is a function of the Mn-Ce composition. Thermodynamics parameters ΔG0, ΔH0 and ΔS0 were calculated. These parameters indicated that the adsorption of phenol onto Mn-Ce was spontaneous and exothermic at 25 and 50 °C.